Marvel-verse. Thanos. - Starlin, Jim; Friedrich, Mike; Englehart, Steve; Nocenti, Ann; Waid, Mark, 1962- (Marvel Worldwide, Inc., 2019)
A collection of classic comic strips featuring the villain Thanos's early battles against Iron Man, Mar-Vel, Mephisto, Spider-man, and Ka-Zar. Includes a bonus story about Thanos and his young daughter, Gamora.